Condom Use Completeness, Perceptions, and Sexual Quality at Most Recent Sexual Event: Results from a U.S. Nationally Representative Probability Sample. Issue 4 (2nd October 2019) - Baldwin, Aleta; Fu, Tsung-Chieh; Reece, Michael; Herbenick, Debby; Dodge, Brian; Sanders, Stephanie A.; Schick, Vanessa; Fortenberry, J. Dennis
Abstract: Objectives: To explore perceptions of condoms associated with complete use and evaluate relationships between condom perceptions, condom use, and sexual quality. Methods: Using data from a U. S. nationally representative probability sample, we assessed individuals' condom use perceptions and related characteristics of their most recent sexual event through bivariate and regression analyses ( n = 234). Results: Most participants reported complete condom use and neutral or positive perceptions of condoms. Though incomplete use was associated with orgasm among women, arousal and pleasure did not differ by gender or duration of condom use. Conclusions: We found no evidence that delayed application or early condom removal increased sexual arousal or pleasure, which may help sexual health promotion interventions address negative cultural ideas about condoms.